Az európai kohézió kihívásai - Veres, Lajos (Közép-Európai Közlemények, 2016)
The concept of territorial cohesion can not be reduced to regional disparities that are based on analyzes on the level of economic relations and of various infrastructures. Interpretation of cohesion between parts and units of European society, rethinking one of the challenges of the future. Increas-ing the value of social cohesion and European responses to demand arising from globalization and geopolitical challenges. The European Union is facing a series of decisions both trans-Atlantic co-operation initiatives and the East, Eurasia challenges with respect. The study presents a novel interpretation of the traditional and the cohesion of the European Union and anticipates resistance to external influences is important to increase, and the importance of new quality requirements. The continuing global economic crisis, international migration and global changes in energy prices are raise awareness of the sensitivity of European Union's economy and society.